Gender Discrimination and Organizational Performance In Public Hospitals In Abia State, Nigeria - Marceline, Onoigboria; Chinelo, Nwagbala Stella; Comfort, Okeke Ngozi (Departemen Ilmu Administrasi FISIP UNHAS, 2024)
Gender inequality is widespread in Nigeria, resulting in women facing unequal opportunities and repercussions. The research focused on organizational efficacy and gender discrimination inside public hospitals in Abia State. This study examines the impact of gender discrimination on organizational performance in public hospitals in Abia State. This study employed a quantitative research methodology, utilizing questionnaires for data collection. The study's population is 3,220, and the Taro Yamane formula was employed to ascertain a sample size of 356 employees. Descriptive statistics examined the data, and the hypothesis was evaluated using Pearson Product Moment Correlation. The study indicated that gender discrimination adversely impacts organizational performance, encompassing operational efficiency, business reputation, and diminished consumer happiness. The research highlights the significance of eliminating gender discrimination in the workplace to enhance organizational performance.